Study of Transverse and Longitudinal Crack Propagation in Human Bone Using the Finite Element Method with MATLAB - Abdullah Dhayea Assi (Al-Khwarizmi College of Engineering – University of Baghdad, 2019)
A finite element is a study that is capable of predicting crack initiation and simulating crack propagation of human bone. The material model is implemented in MATLAB finite element package, which allows extension to any geometry and any load configuration. The fracture mechanics parameters for transverse and longitudinal crack propagation in human bone are analyzed. A fracture toughness as well as stress and strain contour are generated and thoroughly evaluated. Discussion is given on how this knowledge needs to be extended to allow prediction of whole bone fracture from external loading to aid the design of protective systems.